Analysis of Food Vlog Media Integrated Ethnoscience Usage on Students' Critical Thinking Skill - Lestari, Indah Beti; Darmawan, Deni; Dewi, Laksmi; Rahmawati, Yulia (PEDAGOGIA, 2024)
This study investigated the impact of using Food Vlog media in ethnoscience-integrated science learning on students' critical thinking skills. Critical thinking was assessed using a reasoned multiple-choice test. Quantitative data were analyzed through parametric statistical tests, including the paired sample t-test for pretest and posttest results, using SPSS (Statistical Program for Social Science) software. To measure the degree of improvement, an N-Gain test was conducted following the t-test. The paired sample t-test revealed a significance value of 0.000 0.005, indicating that H0 is rejected and Ha is accepted, confirming a significant effect of Food Vlog media on critical thinking skills. The N-Gain test results further showed that improvements in critical thinking skills for SMP and MTs students fell into the medium category. These findings underscore the potential of integrating Food Vlog media with ethnoscience-based science learning as an effective strategy to enhance students' critical thinking abilities. This research suggests that innovative and contextually relevant teaching media can significantly support educational outcomes.